2006
DOI: 10.1007/s10035-006-0020-4
|View full text |Cite
|
Sign up to set email alerts
|

Plug conveying in a horizontal tube

Abstract: Plug conveying along a horizontal tube has been investigated through simulation, using a discrete element simulation approach for the granulate particles and a pressure field approach for the gas. The result is compared with the simulation of the vertical plug conveying. The dynamics of a slug are described by porosity, velocity and force profiles. Their dependence on simulation parameters provides an overall picture of slug conveying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In recent years, some efforts have been made in this direction. For example, Strauß et al 52,53 developed a 3-D CFD-DEM for horizontal and vertical slug flow, where gas flow was described by the Darcy law to avoid CFD effort. Chu and Yu 54 integrated a 3-D DEM model into the commercial CFD package Fluent for the study of gas-solid flow through a bend.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some efforts have been made in this direction. For example, Strauß et al 52,53 developed a 3-D CFD-DEM for horizontal and vertical slug flow, where gas flow was described by the Darcy law to avoid CFD effort. Chu and Yu 54 integrated a 3-D DEM model into the commercial CFD package Fluent for the study of gas-solid flow through a bend.…”
Section: Introductionmentioning
confidence: 99%
“…The slurry is significantly heavier than the clear liquid and slides along the inclined tube until it reaches the bottom 23. Some features of the Boycott effect for gas–particle flows, which are associated with density waves in granular materials were examined experimentally by Raafat et al,24 who observed a nearly stationary structure of density waves, and numerically by Strauss et al25…”
Section: Introductionmentioning
confidence: 99%
“…Much larger systems can be treated this way, but the coarse-graining is justified only in certain situations. An example is the pneumatic transport of a powder in a pipe which is a common process in many industrial applications [12,[47][48][49].…”
Section: Introductionmentioning
confidence: 99%